Characteristics MIMO 2x4 Antenna for 5G Communication System - Yusnita Rahayu; Jodi Wijaya; Elsa Syafitri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper presents the characteristic MIMO 2x4 antenna for 5G communication system. The proposed antenna works at 28 GHz and simulated by using CST simulation software. The antenna uses RT Duroid 5880 substrate with dielectric constant of 2.2. The MIMO antenna consists of eight elements with rectangular patches and inset feeding. The dimension of patch (Wp x Lp) is 6 mm x 8 mm. There are three (3) antenna configurations derived in this paper such as; single element, 1x4 elements and 2x4 elements. The MIMO 1x4 elements antenna configuration is designed based on the single element antenna with the distance between center to center elements antennas of 5 mm. The MIMO 2x4 antenna is formed from the MIMO 1x4 element configuration with the opposite direction. The 2x4 element antenna, a distance between opposite antenna elements is 10 mm. From the simulation results, it is shown that by increasing the number elements of antenna affect to the directivity and the return loss. Antenna with 2x4 elements has 14 dBi of directivity with the return loss of -19 dB. While antenna with 1x4 elements, the directivity obtained is 14.3 dBi with return loss of -18 dB.